2009
DOI: 10.1002/nau.20750
|View full text |Cite
|
Sign up to set email alerts
|

Lower urinary tract symptoms following neurological illness may be influenced by multiple factors: Observations from a neurorehabilitation service in a developing country

Abstract: LUTS in neurological disease may be at variance with the pattern expected based upon level of neurological lesion. Such patients may require further evaluation and consideration should be given to concomitant urological conditions and multiaxial neurological involvement.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 6 publications
0
5
0
Order By: Relevance
“…Second, we must take into account that LUTS following neurological illness may be influenced by multiple factors. For example, the incidence and prevalence of LUTS may rise with increasing progression of the underlying neurological disease ( 9) but also may vary due to the pattern expected based upon type of neurological lesion (10). Moreover, attention should be paid to concomitant urological conditions, benign prostatic hyperplasia (BPH), idiopathic overactive bladder (OAB), urinary infection; such urological conditions are common in aging patients (11).…”
Section: Discussionmentioning
confidence: 99%
“…Second, we must take into account that LUTS following neurological illness may be influenced by multiple factors. For example, the incidence and prevalence of LUTS may rise with increasing progression of the underlying neurological disease ( 9) but also may vary due to the pattern expected based upon type of neurological lesion (10). Moreover, attention should be paid to concomitant urological conditions, benign prostatic hyperplasia (BPH), idiopathic overactive bladder (OAB), urinary infection; such urological conditions are common in aging patients (11).…”
Section: Discussionmentioning
confidence: 99%
“…The most frequent specific urinary symptom in this study was urge incontinence, observed in 31 [70.4%] of all patients. Panicker et al [9] found that incontinence is a common, yet non-specific symptom of neurogenic lower urinary tract dysfunction and in their study was more common in subjects with suprapontine, infrapontine and suprasacral lesions.…”
Section: Resultsmentioning
confidence: 71%
“…In this acute inflammatory spinal cord disease all sensory, motor and sphincter functions are severely affected and this shock stage accompanied by retention of urine. Panicker et al [9] found that patients with infrasacral lesions had significantly more retention than patients with suprapontine, infrapontine or suprasacral lesions [p=0.001]…”
Section: Resultsmentioning
confidence: 99%
“…Two patients with LMF had measurable decreases in pain. Two patients with LM ossification were wheelchair bound, but after surgery and intensive rehabilitation were wheelchair free for at least the 4 years [724,852,853].…”
Section: Plos Onementioning
confidence: 99%